-3(7-4)=-4

Simple and best practice solution for -3(7-4)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(7-4)=-4 equation:


Simplifying
-3(7 + -4) = -4

Combine like terms: 7 + -4 = 3
-3(3) = -4

Multiply -3 * 3
-9 = -4

Solving
-9 = -4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| X+y+9z=-8 | | -1x+-2=1+-2x | | 8x+63=x-21 | | X+6=7.7 | | (-1/3)t=4/3 | | 4/7x-8=-12 | | 19x-6=13x+9 | | 2(3x-3)-4(5x-3)=x(x-3)-x(x+5) | | 3x+2=6x-28 | | (-1/3t=4/3 | | -7(y+2)+3(4y-4)=4(y-3)+8 | | X-61=15 | | A^2=5a+104 | | F(x)=-3x^3-15x^2-12x | | x/-15=-6 | | -36=4w-8 | | 11-2(p+5)=p-5 | | 7x^2+45x+50=0 | | 2(3x-3)-4(5x+3)=x(x-3)-x(x+5) | | 8x-5-11x=9+4x | | 18=(-1/2)y | | 10/1×5/6 | | 3x-11=-23 | | 9(x-1)=9x+11 | | (3x)*(3x)-1=(3x-1)(2x+5) | | 6(y-6)-(y+2)=2 | | V^2-2v+45=5-18v | | F(x)=x^4-8x^2+16 | | -7=u-8 | | 3c-9d+7d+5d= | | 30+3h=6h | | 8x-9y=5 |

Equations solver categories